Clinical management of the pregnant patient undergoing non-obstetric surgery: Review of guidelines. Issue 2 (June 2020) - Okeagu, Chikezie N.; Anandi, Prathima; Gennuso, Sonja; Hyatali, Farees; Stark, Cain W.; Prabhakar, Amit; Cornett, Elyse M.; Urman, Richard D.; Kaye, Alan David
Abstract : The management principles of non-obstetric surgery during pregnancy are important concepts for all health care providers to be cognizant of. The goals of non-obstetric surgery are to ensure maternal safety, maintain the pregnancy, and ensure fetal well-being. In this regard, organogenesis occurs roughly between days 7–57 and thus, certain medications have a higher incidence of fetal teratogenicity in this first trimester. Some examples of common surgeries performed urgently or emergently include appendectomies, ovarian detorsions, bowel obstruction, trauma, and cholecystectomies. The choice of anesthetic technique and the selection of appropriate anesthetic drugs should be guided by indication for surgery, the nature of the surgery, and the site of the surgical procedure. Many of the concerns for any patients undergoing urgent or emergent surgery must be considered by anesthesia providers along with steps to ensure the fetus has the best outcome.